Bridging Education and Industry Gaps through IQF-Based Finansial Management Occupation Mapping - Nainggolan, Bonifasius; Surono, Surono (Politeknik Siber Cerdika Internasional, 2025)
This study aims to bridge the gap between education and industry in financial management by developing a comprehensive occupational map within the Indonesian Qualification Framework (IQF). Employing the methodologies of the Mapping Study (Petersen et al., 2008) and Rapid Assessment Process (RAP) (Beebe, 2005), the research identifies and categorizes essential competencies required for various financial management roles across different qualification levels. The study ensures the validity and traceability of standards by adhering to the principles of the Regional Model Competency Standards (RMCS). Key findings include the identification of critical competencies for each IQF level, which inform curriculum development and support policy-making to align vocational education with industry needs. The results highlight the importance of developing tailored educational programs to enhance employability and career prospects for graduates, contributing to a competitive workforce in Indonesia. This research provides insights and recommendations for future studies, curriculum development, and policy-making in vocational education and training.